Scrutiny of the magnetic properties of ZnO nanoparticles by solid state reaction method. (2022) - Arunkumar, B.; Johnson Jeyakumar, S.; Vasudevan, J.; Jothibas, M.; Sindhya, A.
Abstract: In this work, pure ZnO nanoparticles were prepared by the method of solid state reaction in different temperatures using zinc acetate as a pioneer material. The synthesized ZnO nanoparticles were characterized by the various spectrographic tools. The crystallinity nature and lattice parameters are studied through the XRD patterns and the average crystallite size is found to be 34.5 nm. The absorption peak in the FTIR spectra confirms the presence of functional group, whereas a UV–Vis spectrum is used to determine the optical properties of the sample. Furthermore, surface morphology, electronic structure and the magnetic properties of the ZnO nanoparticles were studied by using the SEM, Photoluminescence and VSM studies respectively. This particular method of synthesis is simple and easiest method to obtain the pure ZnO nanoparticles with high crystallinity in nature. The obtained ZnO, have potential, engineering applications as materials for UV filtering shields with high transparency, luminescent materials without any toxic nature.